The Use of Total Physical Response Method for Different Learning Styles in English Vocabulary Development - Zul Astri (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2018)
Using TPR method in teaching basic vocabulary is a good way for the beginner level of proficiency. The aim of the study is to elaborate how well the Total Physical Response (TPR) method improves the vocabulary of students with different learning styles. The respondents of this study were 30 students of SMP 23 Makassar. The research design was one experiment group with pre and post test. Data were collected with questionnaire from Barsch Learning Style Inventory, vocabulary test, interviews, and classroom observation. Learning Style Inventory (LSI) showed that the most students were visual (40%) and auditory (40%) while 10 % of students were kinesthetic. Some students have combination of learning styles such as visual-auditory (6.67 %) and visual-kinesthetic (3.33 %), while 75 % of visual learners have significant vocabulary development with TPR method. Only 66.67 % auditory learners have significant vocabulary development after giving materials with TPR method. TPR method worked effectively for kinesthetic learning style since 100 % of kinesthetic learners have significant vocabulary development with TPR method. TPR method is also appropriate for visual auditory learners because 100 % of them develop significant vocabularies with the method. Only one visual-kinesthetic learner cannot adapt materials with TPR method, which is indicated by insignificant development with TPR method.